Hard Money and Time Preference: a Bitcoin perspective - Ammous, Saifedean (2022)
Money is what allows individuals to face uncertainty, by controlling and debasing money, governments of the world shift the time preference of individuals to somewhere closer to the present time. This currency inflation disincentivizes saving with societal consequences that go much beyond economics. By giving back to individuals the possibility of saving, Bitcoin emulates what gold did for a number of centuries and provides a much-needed solution to the interference of governments in the money market. The Bitcoin standard will provide for much higher levels of social development, because it will incentivize and facilitate savings as well as the exercise of proper economic calculation.